Government policy attention to aging and mental health among middle aged and older adults: A text-based analysis of chinese municipal reports - Chong Zhuo; Ling Dai; Yuyang Deng (PLoS ONE, 2025)
Objective Population aging has intensified mental health challenges among middle-aged and older adults. This study examines how government attention to aging issues affects mental health outcomes in this demographic. Methods Using data from the China Health and Retirement Longitudinal Study (CHARLS) and municipal government work reports collected between 2011 and 2020, we constructed a government attention index. We employed fixed effects models to analyze the impact on depressive symptoms among middle-aged and older adults, exploring underlying mechanisms and population heterogeneity. Results Higher government attention significantly reduces depressive symptoms among middle-aged and older adults, with stronger effects observed in men and rural populations. Four key mechanisms drive these improvements: environmental enhancement, expanded social welfare, increased adult children visitation, and improved family financial status. Government attention also promotes participation in social and cultural activities but shows no significant impact on adult children’s economic support or sleep duration. Conclusion Government attention to aging issues substantially improves mental health outcomes among middle-aged and older adults. Policymakers should strengthen responses to create more supportive social environments for this growing demographic.